Catalyst-free assembly of giant tris(heteroaryl)methanes: synthesis of novel pharmacophoric triads and model sterically crowded tris(heteroaryl/aryl)methyl cation salts - Abonia, Rodrigo; Gutiérrez, Luisa F.; Insuasty, Braulio; Quiroga, Jairo; Laali, Kenneth K.; Zhao, Chunqing; Borosky, Gabriela L.; Horwitz, Samantha M.; Bunge, Scott D. (Beilstein Journal of Organic Chemistry, 2019)
A series of giant tris(heteroaryl)methanes are easily assembled by one-pot three-component synthesis by simple reflux in ethanol without catalyst or additives. Diversely substituted indoles (Ar1) react with quinoline aldehydes, quinolone aldehydes, chromone aldehydes, and fluorene aldehydes (Ar2CHO) and coumarins (Ar3) in 1:1:1 ratio to form the corresponding tris(heteroaryl)methanes (Ar1Ar2Ar3)CH along with (Ar1Ar1Ar2)CH triads. A series of new 2:1 triads were also synthesized by coupling substituted indoles with Ar2CHO. The coupling reactions could also be carried out in water (at circa 80 °C) but with chemoselectivity favoring (Ar1Ar1Ar2)CH over (Ar1Ar2Ar3)CH. The molecular structure of a representative (Ar1Ar2Ar3)CH triad was confirmed by X-ray analysis. Model tris(heteroaryl/aryl)methylium salts were generated by reaction with DDQ/HPF6 and studied by NMR and by DFT and GIAO-DFT.
Keywords: model heteroarylmethylium salts; multicomponent; one-pot catalyst-free assembly; pharmacophoric triads; three-component synthesis; tris(heteroaryl)methanes; Yonemitsu-type reaction

(untitled) - Dömling, A. (Chem. Rev., 2006)

(untitled) - Shiri, M. (Chem. Rev., 2012)

(untitled) - da Silveira Pinto, L. S.; Couri, M. R. C.; de Souza, M. V. N. (Curr. Org. Synth., 2018)

(untitled) - Mohammadi Ziarani, G.; Moradi, R.; Ahmadi, T.; Lashgari, N. (RSC Adv., 2018)

(untitled) - Vroemans, R.; Verhaegen, Y.; Dieu, M. T. T.; Dehaen, W. (Beilstein J. Org. Chem., 2018)

(untitled) - Shanab, K.; Neudorfer, C.; Schirmer, E.; Spreitzer, H. (Curr. Org. Chem., 2013)

(untitled) - Gu, Y. (Green Chem., 2012)

(untitled) - Nair, V.; Thomas, S.; Mathew, S. C.; Abhilash, K. G. (Tetrahedron, 2006)

(untitled) - Podder, S.; Choudhury, J.; Roy, U. K.; Roy, S. (J. Org. Chem., 2007)

(untitled) - Gomes, R. F. A.; Coelho, J. A. S.; Frade, R. F. M.; Trindade, A. F.; Afonso, C. A. M. (J. Org. Chem., 2015)

(untitled) - Khaksar, S.; Vahdat, S. M.; Gholizadeh, M.; Talesh, S. M. (J. Fluorine Chem., 2012)

(untitled) - Kumar Das, S.; Shagufta; Panda, G. (Tetrahedron Lett., 2005)

Experimental Chemotherapy - Bushby, S. R. M. (Toxicity in Chemotherapy, 1963)

(untitled) - Yamato, M.; Hashigaki, K.; Yasumoto, Y.; Sakai, J.; Luduena, R. F.; Banerjee, A.; Tsukagoshi, S.; Tashiro, T.; Tsuruo, T. (J. Med. Chem., 1987)

(untitled) - Wulff, H.; Miller, M. J.; Hänsel, W.; Grissmer, S.; Cahalan, M. D.; Chandy, K. G. (Proc. Natl. Acad. Sci. U. S. A., 2000)

(untitled) - Mibu, N.; Yokomizo, K.; Uyeda, M.; Sumoto, K. (Chem. Pharm. Bull., 2003)

Fundamentals of the Chemistry and Application of Dyes - Rys, P.; Zollinger, H. (Wiley-Interscience, 1972)

Photochromism: Molecules and Systems - Aldag, R. (Photochromism based on dissociation processes, 1990)

(untitled) - Shchepinov, M. S.; Korshun, V. A. (Chem. Soc. Rev., 2003)

(untitled) - Baker, L. A.; Sun, L.; Crooks, R. M. (Bull. Korean Chem. Soc., 2002)

(untitled) - Sanguinet, L.; Twieg, R. J.; Wiggers, G.; Mao, G.; Singer, K. D.; Petschek, R. G. (Tetrahedron Lett., 2005)

(untitled) - Yu, L.; Li, S.-S.; Li, W.; Yu, S.; Liu, Q.; Xiao, J. (J. Org. Chem., 2018)

(untitled) - Oikawa, Y.; Hirasawa, H.; Yonemitsu, O. (Tetrahedron Lett., 1978)

(untitled) - Lü, C.-W.; Wang, J.-J.; Liu, Y.-H.; Shan, W.-J.; Sun, Q.; Shi, L. (Res. Chem. Intermed., 2017)

(untitled) - Renzetti, A.; Boffa, E.; Colazzo, M.; Gérard, S.; Sapi, J.; Chan, T.-H.; Nakazawa, H.; Villani, C.; Fontana, A. (RSC Adv., 2014)

(untitled) - Gérard, S.; Renzetti, A.; Lefevre, B.; Fontana, A.; de Maria, P.; Sapi, J. (Tetrahedron, 2010)

(untitled) - Viegas-Junior, C.; Danuello, A.; da Silva-Bolzani, V.; Barreiro, E. J.; Fraga, C. A. M. (Curr. Med. Chem., 2007)

Design of Hybrid Molecules for Drug Development - Zhang, S.; Saathoff, J. M.; He, L. (Molecular Hybridization: An Emerging Tool for the Design of Novel Therapeutics for Alzheimer’s Disease, 2017)

(untitled) - Rad-Moghadam, K.; Mohseni, M. (Monatsh. Chem., 2004)

(untitled) - Alizadeh, A.; Ghanbaripour, R.; Zhu, L.-G. (Tetrahedron, 2014)

(untitled) - El-Mekabaty, A.; Mesbah, A.; Fadda, A. A. (J. Heterocycl. Chem., 2017)

Houben-Weyl Methods of Molecular Transformations - Joule, J. A. (Georg Thieme Verlag, 2000)

(untitled) - Mugnaini, C.; Nocerino, S.; Pedani, V.; Pasquini, S.; Tafi, A.; De Chiaro, M.; Bellucci, L.; Valoti, M.; Guida, F.; Luongo, L.; Dragoni, S.; Ligresti, A.; et al. (ChemMedChem, 2012)

(untitled) - Chung, H. J.; Kamli, M. R.; Lee, H. J.; Ha, J. D.; Cho, S. Y.; Lee, J.; Kong, J. Y.; Han, S.-Y. (Biochem. Biophys. Res. Commun., 2014)

(untitled) - Rezayan, A. H.; Hariri, S.; Azerang, P.; Ghavami, G.; Portugal, I.; Sardari, S. (Iran. J. Pharm. Res., 2017)

(untitled) - Hranjec, M.; Lučić, B.; Ratkaj, I.; Kraljević Pavelić, S.; Piantanida, I.; Pavelić, K.; Karminski-Zamola, G. (Eur. J. Med. Chem., 2011)

(untitled) - Desyatkin, V. G.; Beletskaya, I. P. (Synthesis, 2017)

(untitled) - Karthik, G.; Rajasekaran, T.; Sridhar, B.; Subba Reddy, B. V. (Tetrahedron, 2014)

(untitled) - Jadhav, S. D.; Bakshi, D.; Singh, A. (J. Org. Chem., 2015)

(untitled) - Shelke, G. M.; Kumar, A. (Synthesis, 2017)

(untitled) - Deb, M. L.; Deka, B.; Saikia, P. J.; Baruah, P. K. (Tetrahedron Lett., 2017)

(untitled) - Teguh, S. C.; Klonis, N.; Duffy, S.; Lucantoni, L.; Avery, V. M.; Hutton, C. A.; Baell, J. B.; Tilley, L. (J. Med. Chem., 2013)

(untitled) - Lin, W.; Yuan, L.; Cao, Z.; Feng, J.; Feng, Y. (Dyes Pigm., 2009)

(untitled) - Khan, M. N.; Pal, S.; Karamthulla, S.; Choudhury, L. H. (New J. Chem., 2014)

(untitled) - Oelerich, J.; Roelfes, G. (Org. Biomol. Chem., 2015)

(untitled) - Shao, Z.; Xu, L.; Wang, L.; Wei, H.; Xiao, J. (Org. Biomol. Chem., 2014)

(untitled) - Jennings, J. J.; Bhatt, C. P.; Franz, A. K. (J. Org. Chem., 2016)

(untitled) - Prabhakar, M.; Reddy, G. N.; Srinu, G.; Manjulatha, K.; Prasad, J. V.; Kumar, S. P.; Srinivas, O.; Iqbal, J.; Kumar, K. A. (Synlett, 2010)

(untitled) - Shiri, M.; Zolfigol, M. A.; Kruger, H. G.; Tanbakouchian, Z. (Chem. Rev., 2010)

(untitled) - Kottawar, S. S.; Siddiqui, S. A.; Pendalwar, S. S.; Jadhav, W. N.; Bhusare, S. R. (Res. Chem. Intermed., 2014)

(untitled) - Shelke, G. M.; Rao, V. K.; Tiwari, R. K.; Chhikara, B. S.; Parang, K.; Kumar, A. (RSC Adv., 2013)

(untitled) - Appendino, G.; Cicione, L.; Minassi, A. (Tetrahedron Lett., 2009)

(untitled) - Mousavizadeh, F.; Hekmatshoar, R.; Beheshtiha, S. Y. S.; Rahnamafar, R. (Synth. Commun., 2014)

(untitled) - Laali, K. K.; Insuasty, D.; Abonia, R.; Insuasty, B.; Bunge, S. D. (Tetrahedron Lett., 2014)

(untitled) - Ramírez-Prada, J.; Robledo, S. M.; Vélez, I. D.; del Pilar Crespo, M.; Quiroga, J.; Abonia, R.; Montoya, A.; Svetaz, L.; Zacchino, S.; Insuasty, B. (Eur. J. Med. Chem., 2017)

(untitled) - Abonia, R.; Insuasty, D.; Castillo, J.; Insuasty, B.; Quiroga, J.; Nogueras, M.; Cobo, J. (Eur. J. Med. Chem., 2012)

(untitled) - Insuasty, D.; Abonia, R.; Insuasty, B.; Quiroga, J.; Laali, K. K.; Nogueras, M.; Cobo, J. (ACS Comb. Sci., 2017)

(untitled) - Kong, A.; Han, X.; Lu, X. (Org. Lett., 2006)

(untitled) - Meth-Cohn, O.; Narine, B. (Tetrahedron Lett., 1978)

(untitled) - Meth-Cohn, O.; Narine, B.; Tarnowski, B. (J. Chem. Soc., Perkin Trans. 1, 1981)

(untitled) - Oda, M.; Fukuta, A.; Kajioka, T.; Uchiyama, T.; Kainuma, H.; Miyatake, R.; Kuroda, S. (Tetrahedron, 2000)
See for an example.

Recent Developments in Carbocation and Onium Ion Chemistry - Ito, S.; Akimoto, K.; Morita, N. (ACS, 2007)
See for DDQ/HPF6 previously employed for generation of tri(1-azulenyl)methyl cation salts.

(untitled) - Ito, S.; Morita, N.; Asao, T. (Bull. Chem. Soc. Jpn., 1995)

(untitled) - Pfeuffer, L.; Mueller, J.; Pindur, U. (Chimia, 1985)
See for 3-indolylmethylethoxycarbenium BF4 salt.

(untitled) - Pindur, U.; Mueller, J. (Chem.-Ztg., 1986)
See for a UV–vis study of diindolylmethylium.

Gaussian 09, Revision E.01 (Gaussian, Inc., 2009)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Miehlich, B.; Savin, A.; Stoll, H.; Preuss, H. (Chem. Phys. Lett., 1989)

(untitled) - Wolinski, K.; Hinton, J. F.; Pulay, P. (J. Am. Chem. Soc., 1990)

(untitled) - Ditchfield, R. (Mol. Phys., 1974)

APEX II (Bruker AXS, Inc., Analytical X-ray Systems, 2005)

SAINT, Version 6.45A (Bruker AXS, Inc., Analytical X-ray Systems, 2003)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Adv., 2015)

SHELXTL, V6.12 (Bruker AXS, Inc., Analytical X-ray Systems, 2002)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)

DIAMOND, Bonn, Germany (Crystal Impact GbR, 1999)